Silent Meckel’s diverticulum in an acute abdomen of adolescence - Pasupathy, Umapathy; Ramasundaram, Madhu; Jayapalan, Dinesh Kumar; Bharathi, Umaserma; Francis, Litha (International Journal of Contemporary Pediatrics, 2024)
Meckel's diverticulum is common congenital abnormality which is common in less than 2 years of age, mostly asymptomatic and may complications such as intestinal blockage, gastrointestinal bleeding, and perforation. It may rarely present with gangrenous Meckel’s diverticulum. A 13-year-old child brought with complaint abdominal pain for a month and abdominal distention, vomiting, fever for two days. No history of bleeding per rectum. On clinical examination, child febrile with tenderness in the lower abdomen and guarding in the right iliac fossa. Blood workup was normal. A CECT scan of whole abdomen revealed an enlarged appendix filled with fluid, and possible perforation tip of appendix. The imaging findings indicated a possible case of acute appendicitis, with signs of perforation and the presence of an abscess or collection near the appendix. The child underwent a laparoscopic appendectomy. Intraoperatively, it was found that the appendix was inflamed and had adhesions to the small bowel, abdominal wall, sigmoid colon, and urinary bladder. A bowel walk revealed dilated loops of the small bowel, and approximately three feet from the junction of the small and large intestines, a gangrenous Meckel's diverticulum was found. Consequently, a laparoscopic-assisted Meckel's resection and ileoileal anastomosis were performed. After surgical procedure, child improved symptomatically. Diverticulitis has multi facet clinical presentation and it can also occur along with other gastrointestinal conditions. Hence approaching any gastrointestinal condition, also should have suspicion on diverticulitis to avoid the complications of diverticulitis.